1999
DOI: 10.2165/00002018-199920050-00003
|View full text |Cite
|
Sign up to set email alerts
|

Safety Issues Concerning the Use of Disulfiram in Treating Alcohol Dependence

Abstract: Disulfiram is known to cause hepatitis, which is sometimes fatal. The best estimate of the frequency of disulfiram-induced fatal hepatitis is 1 case in 30,000 patients treated/year. Its appears to be more common in patients given disulfiram for the treatment of nickel sensitivity. Frequent blood testing for liver function is probably not necessary, but patients taking disulfiram should be in regular contact with a physician. There are rare reports of psychosis and confusional states in conjunction with disulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
130
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(131 citation statements)
references
References 38 publications
0
130
0
1
Order By: Relevance
“…DARs were reported on 29 occasions [106] but none led to a dose reduction, and the authors concluded that disulfiram was well tolerated when given as part of a wider treatment programme. A small cohort study of more than 50 weeks duration (disulfiram cohort study in an Indian population (125mg/d) [111] showed an excess of skin rashes, supporting an earlier observation that there may be greater sensitivity to the adverse effects of disulfiram in Indian compared to Western patients [112]. A study in adolescents [113] found it to be well tolerated with no significant differences in reported adverse events between disulfiram (200mg/d) and placebo.…”
Section: Main Summary Of Adverse Effectsmentioning
confidence: 75%
See 2 more Smart Citations
“…DARs were reported on 29 occasions [106] but none led to a dose reduction, and the authors concluded that disulfiram was well tolerated when given as part of a wider treatment programme. A small cohort study of more than 50 weeks duration (disulfiram cohort study in an Indian population (125mg/d) [111] showed an excess of skin rashes, supporting an earlier observation that there may be greater sensitivity to the adverse effects of disulfiram in Indian compared to Western patients [112]. A study in adolescents [113] found it to be well tolerated with no significant differences in reported adverse events between disulfiram (200mg/d) and placebo.…”
Section: Main Summary Of Adverse Effectsmentioning
confidence: 75%
“…Early studies of disulfiram used much higher doses (1-3g daily) causing a higher burden of serious adverse effects and DAR, including death [112]. In one variable dose study, 500mg doses of disulfiram were much less tolerated than 250mg with all withdrawals due to adverse events in the 500mg group [114].…”
Section: Main Summary Of Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatric complications appear to be more common with the use of disulfiram in India than in Western Countries [5].…”
mentioning
confidence: 94%
“…(3) Disulfiram can be viewed as a drug with a moderate record of adverse effects. Alcohol dependence, for which it can be helpful treatment, is associated with a high morbidity and mortality [5]. (4) Relapse rate is very high, Helander A (1998) reported 80% of his patients returned to drinking very soon on discontinuation of disulfiram therapy [11].…”
mentioning
confidence: 99%